2010
DOI: 10.1287/orsc.1080.0394
|View full text |Cite
|
Sign up to set email alerts
|

A Recursive Perspective on Discursive Legitimation and Organizational Action in Mergers and Acquisitions

Abstract: This paper challenges the predominant view that legitimation is merely a specific phase in merger or acquisition processes. We argue that a better understanding of postmerger organizational dynamics calls for conceptualization of discursive legitimation as an inherent part of unfolding merger processes. In particular, we focus on the recursive relationship between legitimation and organizational action. We have two objectives: to outline a theoretical model that helps one to understand the dynamics of discursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
288
2
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(310 citation statements)
references
References 81 publications
7
288
2
13
Order By: Relevance
“…Exceptions are offered by Vaara and Monin (2010), who studied the dynamics of discursive legitimation in PMI and highlighted the risk that overly positive communication can lead to a legitimacy crisis; and by Vaara and Tienari (2011), who examined how organizational actors and the media used various discursive resources and forms of storytelling to impact the course of PMI. On the whole, however, we know little regarding communication practices and tools in PMI.…”
Section: Tools Of Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Exceptions are offered by Vaara and Monin (2010), who studied the dynamics of discursive legitimation in PMI and highlighted the risk that overly positive communication can lead to a legitimacy crisis; and by Vaara and Tienari (2011), who examined how organizational actors and the media used various discursive resources and forms of storytelling to impact the course of PMI. On the whole, however, we know little regarding communication practices and tools in PMI.…”
Section: Tools Of Communicationmentioning
confidence: 99%
“…Similarly, in the PMI context, senior managers -particularly from the acquiring firmwill need to devote attention to external parties like industry analysts, shareholders and the media (Vaara & Monin, 2010;Vaara & Tienari, 2011). Acquirers often make predictions to shareholders and industry analysts regarding synergies that will be realized from an acquisition, and senior management will likely be focused on achieving those targets.…”
Section: Emotionalitymentioning
confidence: 99%
“…Yet remembering and forgetting are two sides of the same memory phenomenon. Like voicing and self-editing (Bernstein, 1964;Chafe, 1980), sensegiving and sensehiding (Vaara & Monin, 2009) or learning and un-learning (Brunsson, 1998) (Anderson & Bjork, 1994;Anderson & Spellman, 1995;Douglas, 1986;MacLeod & Macrae, 2001;Misztal, 2003).…”
Section: Implications For Organizational Identity Researchmentioning
confidence: 99%
“…Their intent was likely a transformation PMI approach. It has been suggested that this approach is not efficient because the available PMI time is often insufficient and the identification of the necessary ISs could create resistance and political struggle (Wijnhoven et al, 2006;Vaara & Monin, 2010). Suncorp and Promina had multiple IT applications, each with its own practices and knowledge bases.…”
Section: Absorption and Transformation Pragmatic Boundariesmentioning
confidence: 99%
“…Post-merger integration (PMI) is the process of actual merger value-creation that will hopefully materialize when the organizations are amalgamated (Larsson & Finkelstein, 1999). Despite the anticipated benefits of a merger, high failure rates have been reported (Yetton, Henningsson, & Bjorn-Andersen, 2013), which suggests inherent complexities in managing PMI (Mehta & Hirschheim, 2007;Vieru & Rivard, 2014b) and associated challenges that are yet to be fully understood (Vaara & Monin, 2010).…”
Section: Introductionmentioning
confidence: 99%